Effects of pH-equilibrated ocean alkalinization on macro-benthic calcifiers: A mesocosm study from the port of La Spezia (Italy) - Davide Calvi; Sara Groppelli; Federico Comazzi; Samira Jamali Alamooti; Arianna Azzellino; Piero Macchi; Daniela Basso (Marine Pollution Bulletin, 2026)

Upper Tortonian skeletal assemblages of phosphatic hardgrounds record upwelling pulses and internal-wave processes (Latium–Abruzzi Platform, Italy) - Daniela Basso; Valentina Alice Bracchi; Irene Cornacchia; Alessandro Mancini; Marco Brandano (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Quantitative analysis of Upper Miocene Mediterranean reef carbonates: A tool for reconstructing palaeoenvironmental gradients - Giovanni Coletti; Alberto Vimercati; Francesca R. Bosellini; Luca Mariani; Adriano Guido; Alessandro Vescogni; Jesús Reolid; Gerald Auer; Daniela Basso; Alberto Collareta; Giulia Bosio; Or Mordecai Bialik (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Editorial preface to special issue: The Mediterranean tropical legacy: perspectives from Upper Miocene marine environments - Francesca R. Bosellini; Giovanni Coletti; Juan C. Braga; Daniela Basso (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Unveiling the origin of enigmatic seabed morphologies on the Cape Licosa ridge (Italy) - Valentina Alice Bracchi; Sara Innangi; Renato Tonielli; Gemma Aiello; Pietro Bazzicalupo; Daniela Basso; Davide Vernazzani; Valentina Grande (Marine Geology, 2026)

Assessment of Soil Analytical Methods and Black Oats (Avena strigosa L.) Morphological and Physiological Responses to Copper Toxicity - Paulo Ademar Avelar Ferreira; Cesar Cella; Leandro Souza da Silva; Gerson Laerson Drescher; Daniela Basso Facco; Camila Peligrinotti Tarouco; Fábio Joel Kochem Mallmann; Adriele Tassinari; Gustavo Brunetto (Journal of Soil Science and Plant Nutrition, 2026)
Copper (Cu) accumulation is a major concern in agricultural production systems due to potential toxicity to plants and environmental contamination. Soil testing is the best available means to determine nutrient availability, but different analytical methods extract various amounts of Cu. Hence, critical levels of Cu toxicity need to be defined for multiple extractants to ensure adequate interpretation of potential element toxicity to plants. Objective: Our study aimed to (a) evaluate Cu availability in soils using three different chemical extractants (CaCl2, Mehlich-1, and EDTA) and (b) identify black oats ( Avena strigosa L. ) physiological responses that can be used as indicators of Cu phytotoxicity potential and assist in defining critical Cu toxicity levels. A greenhouse experiment was conducted with three soils previously incubated with different Cu rates. Soil Cu availability was analyzed by CaCl2 0.01 mol L− 1, Mehlich-1, and EDTA, and the concentrations were correlated to black oats relative dry matter yield and plant photosynthetic parameters (i.e., photosynthetic rate, stomatal conductance, total chlorophylls, and carotenoids) of plant growth in soil without Cu application. Soil testing methods recovered different amounts of Cu in the following order: EDTA > Mehlich-1 > CaCl2, with CaCl2 being the method with the lowest sensitivity to assess Cu availability. Soil clay content affected Mehlich-1 Cu extractions, with concentration decreasing for soils with greater clay content. The highest plant Cu concentrations were observed in the roots, with little variation in concentrations in the shoot. The EDTA and Mehlich-1analytical methods showed different critical Cu toxicity concentrations for black oats dry matter and photosynthetic parameters. The analytical methods showed different Cu extraction capacities, with concentrations increasing in the following order: EDTA > Mehlich-1 > CaCl₂, and concentration differences being influenced by soil clay and organic matter contents. Therefore, critical Cu phytotoxicity levels should consider both soil characteristics and the extraction method used. The inhibitory concentrations IC25 and IC50 values were consistent for biomass and photosynthetic rate, indicating the latter as an effective non-destructive method to monitor plant metal-induced stress. However, interactions with other nutrients and abiotic stresses still require further investigation.

The response of phytoplankton to pH-equilibrated ocean alkalinization: A mesocosm experiment with harbour waters - Sara Groppelli; Davide Calvi; Federico Comazzi; Samira Jamali Alamooti; Arianna Azzellino; Eleonora Barbaccia; Sarah Caronni; Piero Macchi; Guido Raos; Daniela Basso (Marine Pollution Bulletin, 2026)

Caught in the act: calcareous algae creating undescribed morphologies of mesophotic algal reef - Sara Innangi; Valentina Alice Bracchi; Daniela Basso; Renato Tonielli (Marine Geology, 2025)

Plankton do not care: Minimal effects of ocean liming on plankton growth and grazing in the Eastern Mediterranean - Claudia Traboni; Ariadna C. Nocera; Filomena Romano; Justine Courboulès; Christos Chantzaras; Iordanis Magiopoulos; Selene Varliero; Daniela Basso; Paraskevi Pitta (Limnology and Oceanography, 2025)
Increasing CO 2 emissions have led to the development of CO 2 removal strategies to counteract ocean acidification. Among these, ocean alkalinity enhancement techniques, particularly ocean liming, may represent a promising approach to restore seawater pH and boost CO 2 sequestration. Yet, the impact of liming on plankton communities remains underexplored. In the framework of a mesocosm experiment, we conducted three dilution incubations to assess natural plankton response (abundance, composition, growth, grazing, diet, and food selectivity) to liming, achieved with calcium hydroxide (Ca(OH) 2 ) additions. Experiments included two liming treatments (low concentration, and high concentration) and a control treatment without Ca(OH) 2 . The community was dominated by small‐sized plankton (bacteria, Synechococcus and pigmented picoflagellates), outnumbering larger diatoms, dinoflagellates, and ciliates. While chlorophyll a , heterotrophic bacteria, and pigmented picoflagellates remained stable across treatments, the abundance of Synechococcus and dinoflagellates increased, whereas diatoms and ciliates declined particularly under high Ca(OH) 2 . Growth and grazing rates were largely unaffected by alkalinity, except for increased growth in pigmented picoflagellates upon liming. Microzooplankton showed low ingestion of Synechococcus and pigmented picoflagellates and higher intake of diatoms, dinoflagellates, and ciliates. Food selectivity was unresponsive to liming, as the grazers selected prey based on size, regardless of Ca(OH) 2 concentrations. Increased alkalinity and pH, and the parallel effect of trophic cascades might have driven nutrient fluctuations and shaped downstream trophic interactions. Despite positive responses highlighted in this study, further research is needed to explore liming potentiality on a wider range of food‐web components and larger scales in the framework of ocean alkalinity enhancement research.

CoDeMap: a classification scheme for benthic habitats from the coast to the deep sea in the Mediterranean and Black Sea - Valentina Grande; Lorenzo Angeletti; Mariacristina Prampolini; Giorgio Castellan; Giacomo Dalla Valle; Simonetta Fraschetti; Daniela Basso; Dimitar Berov; Valentina A. Bracchi; Frine Cardone; Giovanni Chimienti; Annalisa Falace; et al. (Frontiers in Marine Science, 2025)
The spatial representation of benthic habitats is essential across various applications, such as biodiversity monitoring, ecosystem management and conservation, and maritime spatial planning. In this context, classification schemes provide a universally understandable framework to characterize and chart the seafloor. This work introduces the Coast to Deep Mapping (CoDeMap) classification scheme for benthic habitats from the coast to the deep-sea environments. It consists of three main components (Morphology, Substrate and Biology) and it is conceived as a practical tool for users from various backgrounds who need to organize and interpret marine observational data, as well as characterize and map seafloors. While primarily developed for the Mediterranean Sea and the Black Sea, CoDeMap serves as a foundational framework that can be adapted to address any current or future similar request worldwide.

The effect of ocean alkalinity enhancement on zooplankton standing stock and community composition in the Eastern Mediterranean Sea: a mesocosm study - Ariadna C. Nocera; Claudia Traboni; Justine Courboulès; Filomena Romano; Christos Chantzaras; Iordanis Magiopoulos; Selene Varliero; Arianna Azzellino; Pietro Bazzicalupo; Piero Macchi; Guido Raos; Daniela Basso; et al. (Marine Environmental Research, 2025)

A thousand-year journey of lithification: CT-analysis and radiocarbon dating of algal reef from Central Mediterranean - Pietro Bazzicalupo; Valentina Alice Bracchi; Mara Cipriani; Adriano Guido; Antonietta Rosso; Rossana Sanfilippo; Francesco Maspero; Anna Galli; Elena de Ponti; Daniela Basso (Marine Geology, 2025)

Mapping benthic marine habitats featuring coralligenous bioconstructions: a new approach to support geobiological research - Giuseppe Maruca; Mara Cipriani; Rocco Dominici; Gianpietro Imbrogno; Giovanni Vespasiano; Carmine Apollaro; Francesco Perri; Fabio Bruno; Antonio Lagudi; Umberto Severino; Valentina A. Bracchi; Daniela Basso; et al. (Ocean Science, 2025)
Seabed mapping represents a very useful tool for seascape characterization and benthic habitat study and requires advanced technologies for acquiring, processing, and interpreting remote data. Particularly, acoustic instruments, such as high-resolution swath bathymetry sounders (i.e., multibeam echosounder: MBES), allow us to recognize, identify, and map the extension of benthic habitats without applying invasive mechanical procedures. Bathymetry and backscatter (BS) data are crucial to perform modern habitat mapping. Although the acquisition and processing of bathymetric data follow standardized procedure (e.g., Hydrographic Organization guidelines), and recent studies have proposed recommendations for backscatter acquisition and processing, a broadly validated methodological approach, integrating geomorphometric analysis for benthic habitat mapping, is still lacking. In this work, a new approach for benthic habitat mapping, with a focus on coralligenous bioconstructions, was developed using the open-source software QGIS. This methodology, tested within the Isola Capo Rizzuto Marine Protected Area (Calabria, Italy), is designed to be freely reproducible by researchers working in the field of marine ecosystem monitoring and conservation. Through the proposed mapping procedure, it is possible to (i) identify benthic habitats in selected study areas by combining bathymetry and BS data with geomorphological indices performed in QGIS and (ii) quantitatively define the 2D and 3D distribution of coralligenous bioconstructions in terms of surface covered, thickness, and volume. Moreover, the statistical analysis of quantitative morphometric data allowed for comparison of geometric characteristics of different coralligenous morphotypes. The obtained results, combined with improvement of minimally invasive sampling and geobiological–geochemical characterization, can contribute to the development of protocols aimed at monitoring marine bioconstructed ecosystems, many of which are protected by national and international regulations due to their importance for Mediterranean biodiversity preservation, and plan actions for their protection and persistence.

Mesophotic banks of Dendrophyllia ramea offshore Marzamemi (Sicily, Ionian Sea): a habitat classification model - Valentina Alice Bracchi; Luca Marino; Verena Voulaz; Alessandra Savini; Luca Fallati; Andrea Giulia Varzi; Pietro Bazzicalupo; Daniela Basso (Continental Shelf Research, 2025)

Mollusk diversity of coralligenous build-ups in the southwestern Ionian Sea - VALENTINA ALICE BRACCHI; MAURO PIETRO NEGRI; PIETRO BAZZICALUPO; MARCO BERTOLINO; MARA CIPRIANI; GEMMA DONATO; ADRIANO GUIDO; ANTONIETTA ROSSO; ROSSANA SANFILIPPO; FRANCESCO SCIUTO; DANIELA BASSO (Mediterranean Marine Science, 2025)
The coralligenous algal reefs are priority ecosystems of the Circalittoral zone of the Mediterranean Sea shelves. Characterized by decimeter- to meter-high build-ups, these reefs create a complex environment hosting high biodiversity. Despite their common occurrence, the roles of mollusks within coralligenous structures have been overlooked until recently. To address this gap, the CRESCIBLUREEF project investigated samples of coralligenous build-ups collected from diverse settings at similar depths (33.5- 37.2 m) along the SE Sicilian shelf (Italy). In the studied samples, we identified 158 mollusk species –mostly autochthonous– including some previously undocumented for this habitat. Our study underscores the importance of using appropriate sampling techniques in studying mollusk biodiversity and the pivotal role algal reefs play in supporting a diverse array of mollusk species, spanning not only those associated with hard substrates but also epiphytic, cryptic, and infaunal species. Despite the samples being sourced at similar depths, multivariate statistical analysis based on mollusk abundance indicated a distinction between coralligenous morphologies in the living assemblage. Overall, our findings contribute to improving the knowledge on mollusks associated with coralligenous reefs and emphasize the valuable role of mollusks as sensitive indicators of environmental conditions, confirming their vital importance in conservation science and benthic ecology.

Antagonistic activity of autochthonous strains of Bacillus amyloliquefaciens and Bacillus velezensis against fungi and oomycetes associated to damping off - Ricardo Puche; Vanesa Basso; María Verónica Fumero; Daniela Medeot; Edgardo Jofré (Rhizosphere, 2025)

Micro- and ultrastructural features for the distinction of Phymatolithon lusitanicum from Phymatolithon calcareum - Francesca Panizzuti; Aurora Giorgi; Maggie D. Johnson; Daniela Basso (Aquatic Botany, 2025)

The Baroch Nala section (NE Pakistan): A new PETM standard for the eastern Tethys - Mubashir Ali; Giovanni Coletti; Eduardo Garzanti; Thierry Adatte; Sébastien Castelltort; Pietro Sternai; Andrea Benedetti; Elisa Malinverno; Luca Mariani; Jorge E. Spangenberg; Suleman Khan; Daniela Basso; et al. (Marine and Petroleum Geology, 2025)

Biodiversity associated with a coralligenous build-up off Sicily (Ionian Sea) - Gemma Donato; Rossana Sanfilippo; Daniela Basso; Pietro Bazzicalupo; Marco Bertolino; Valentina Alice Bracchi; Mara Cipriani; Francesco D’Alpa; Adriano Guido; Mauro Pietro Negri; Francesco Sciuto; Donatella Serio; et al. (Regional Studies in Marine Science, 2024)

New chronology for submerged relict paleoshorelines and associated rates of crustal vertical movements offshore the Marzamemi village, Sicily (Southern Italy) - Andrea Giulia Varzi; Marco Meschis; Luca Fallati; Giovanni Scicchitano; Vincenzo De Santis; Giovanni Scardino; Daniela Basso; Valentina Alice Bracchi; Alessandra Savini (Marine Geology, 2024)

ENSO effects on the relationship between aerosols and evapotranspiration in the south of the Amazon biome - Rafael Palácios; Daniela Castagna; Luzinete Barbosa; Adilson P. Souza; Breno Imbiriba; Cornélio A. Zolin; Danielle Nassarden; Leilane Duarte; Fernando G. Morais; Marco A. Franco; Glauber Cirino; Paulo Kuhn; et al. (Environmental Research, 2024)

Short-term impact assessment of ocean liming: A copepod exposure test - Elisa Camatti; Silvia Valsecchi; Stefano Caserini; Eleonora Barbaccia; Chiara Santinelli; Daniela Basso; Arianna Azzellino (Marine Pollution Bulletin, 2024)

Enhancing adsorption capacity of magnetic magnesium-aluminum layered double hydroxide by surface modification with sodium dodecyl sulfate for efficient removal of organic contaminants - Ana Caroline Reis Meira; João Vitor Gehlen Zago; Bruna Ghellere Tremarin; Daniela Zambelli Mezalira; Ana Cristina Trindade Cursino; Alesandro Bail; Rodrigo Leonardo de Oliveira Basso; Renata Mello Giona (Journal of Environmental Chemical Engineering, 2023)

Growth, biochemical and physiological response of grapevine rootstocks to copper excess in nutrient solution - Edicarla Trentin; Paulo Ademar Avelar Ferreira; Felipe Klein Ricachenevsky; Daniela Basso Facco; Rodrigo Knevitz Hammerschmitt; Letícia Morsch; Camila Peligrinotti Tarouco; Fernando Teixeira Nicoloso; Maristela Machado Araujo; Álvaro Luís Pasquetti Berghetti; George Wellington Bastos de Melo; Gustavo Brunetto (South African Journal of Botany, 2023)

Levelling-up rhodolith-bed science to address global-scale conservation challenges - Fernando Tuya; Nadine Schubert; Julio Aguirre; Daniela Basso; Eduardo O. Bastos; Flávio Berchez; Angelo F. Bernardino; Néstor E. Bosch; Heidi L. Burdett; Fernando Espino; Cindy Fernández-Gárcia; Ronaldo B. Francini-Filho; et al. (Science of The Total Environment, 2023)

Chemical speciation of copper and manganese in solution of a copper-contaminated soil and young grapevine growth with amendment application - Daniela Basso FACCO; Edicarla TRENTIN; Gerson Laerson DRESCHER; Rodrigo Knevitz HAMMERSCHMITT; Carlos Alberto CERETTA; Leandro Souza DA SILVA; Gustavo BRUNETTO; Paulo Ademar Avelar FERREIRA (Pedosphere, 2023)

The Bryozoan Margaretta cereoides as Habitat-Former in the Coralligenous of Marzamemi (SE Sicily, Mediterranean Sea) - Antonietta Rosso; Gemma Donato; Rossana Sanfilippo; Donatella Serio; Francesco Sciuto; Francesco D’Alpa; Valentina Alice Bracchi; Mauro Pietro Negri; Daniela Basso (Journal of Marine Science and Engineering, 2023)
Although several bryozoans are considered habitat-former species, allowing colonisation by epibionts and promoting biodiversity, studies dealt so far with only some, usually constructional, species. In this context, the present study focuses on the epibiosis found on the erect mineralised but flexible species Margaretta cereoides, contributing with some macroalgae to the canopy formation on a coralligenous build-up collected at 36.7 m depth offshore Marzamemi (Ionian Sea, Mediterranean) in the frame of the project CRESCIBLUREEF. Focusing on bryozoans and serpulids we documented high diversity (species richness) on the investigated substrata (M. cereoides, Flabellia petiolata, Peyssonnelia rubra, Osmundaria volubilis and all other fleshy algae including Phyllophora crispa). Diversity, total number of colonies/specimens hosted, and number of colonies/specimens per cm2 are higher on M. cereoides than on algae, possibly in relation with the morphology, robustness and persistence of the surface offered by the bryozoan contrasting with the flexible and ephemeral nature of most algae, often provided with chemical defenses. Bryozoan and even more serpulid epibiont diversity on M. cereoides is also higher than those reported for studied species in the Mediterranean and for Flustra foliacea from North Europe.

Circulating cell-free DNA in health and disease — the relationship to health behaviours, ageing phenotypes and metabolomics - Laura Kananen; Mikko Hurme; Alexander Bürkle; Maria Moreno-Villanueva; Jürgen Bernhardt; Florence Debacq-Chainiaux; Beatrix Grubeck-Loebenstein; Marco Malavolta; Andrea Basso; Francesco Piacenza; Sebastiano Collino; Efstathios S. Gonos; et al. (GeroScience, 2023)
Circulating cell-free DNA (cf-DNA) has emerged as a promising biomarker of ageing, tissue damage and cellular stress. However, less is known about health behaviours, ageing phenotypes and metabolic processes that lead to elevated cf-DNA levels. We sought to analyse the relationship of circulating cf-DNA level to age, sex, smoking, physical activity, vegetable consumption, ageing phenotypes (physical functioning, the number of diseases, frailty) and an extensive panel of biomarkers including blood and urine metabolites and inflammatory markers in three human cohorts (N = 5385; 17–82 years). The relationships were assessed using correlation statistics, and linear and penalised regressions (the Lasso), also stratified by sex. cf-DNA levels were significantly higher in men than in women, and especially in middle-aged men and women who smoke, and in older more frail individuals. Correlation statistics of biomarker data showed that cf-DNA level was higher with elevated inflammation (C-reactive protein, interleukin-6), and higher levels of homocysteine, and proportion of red blood cells and lower levels of ascorbic acid. Inflammation (C-reactive protein, glycoprotein acetylation), amino acids (isoleucine, leucine, tyrosine), and ketogenesis (3-hydroxybutyrate) were included in the cf-DNA level-related biomarker profiles in at least two of the cohorts. In conclusion, circulating cf-DNA level is different by sex, and related to health behaviour, health decline and metabolic processes common in health and disease. These results can inform future studies where epidemiological and biological pathways of cf-DNA are to be analysed in details, and for studies evaluating cf-DNA as a potential clinical marker.

Anti-Aspergillus fumigatus IgG in patients with bronchiectasis and its relationship with clinical outcome - Mariana Rodrigues Trápaga; Vanice Rodrigues Poester; Karine Ortiz Sanchotene; Aryse Martins Melo; Jéssica Louise Benelli; Rossana Patricia Basso; Gabriel Baracy Klafke; Daniela Fernandes Ramos; Cristina Veríssimo; Raquel Sabino; David A. Stevens; Melissa Orzechowski Xavier (Archives of Microbiology, 2022)

ClC-2-like Chloride Current Alterations in a Cell Model of Spinal and Bulbar Muscular Atrophy, a Polyglutamine Disease - Vladimir A. Martínez-Rojas; Aura M. Jiménez-Garduño; Daniela Michelatti; Laura Tosatto; Marta Marchioretto; Daniele Arosio; Manuela Basso; Maria Pennuto; Carlo Musio (Journal of Molecular Neuroscience, 2021)

Growth rates and ecology of coralline rhodoliths from the Ras Ghamila back reef lagoon, Red Sea - Annalisa Caragnano; Daniela Basso; Graziella Rodondi (Marine Ecology, 2016)
Rhodoliths are important marine carbonate producers that provide habitat for several marine organisms, and are threatened by ongoing global climate change. Meter‐sized sedimentary patches rich in living rhodoliths, interspersed among corals, were discovered in the back reef of Ras Ghamila lagoon, Southern Sinai, at less than 1 m water depth. In this shallow and relatively sheltered subtropical environment, rhodoliths were found to be monospecific or oligospecific, spheroidal, 3.5 to 9.4 cm in maximum diameter, with warty/lumpy or fruticose (protuberance degree IV ) growth forms, and corresponded to the unattached branches or praline type. They grew in bright light under seasonal, moderate, wind‐driven water motion. The dominant rhodolith‐forming species recorded were: Lithophyllum kotschyanum , Porolithon onkodes , Hydrolithon sp. and three species of Neogoniolithon: Neogoniolithon fosliei, Neogoniolithon brassica‐florida , and an undescribed species noted in the text as Neogoniolithon sp. A total of 38 Alizarin‐stained rhodoliths was released in the field and collected after 1 year. They showed different banding patterns (alternating long and short cells) that revealed seasonal growth, with the lowest rates occurring in winter for all species, and an additional summer growth slackening in Neogoniolithon fosliei . Lithophyllum kotschyanum presented evidence of occasional growth cessation, possibly due to temporary burial. The observed annual growth rate of rhodoliths was unrelated to their size. The mean accretion rates were 1.08 mm · year −1 in L. kotschyanum , 0.75 mm · year −1 in P. onkodes , 0.49 mm · year −1 in Hydrolithon sp., 0.85 mm mm · year −1 in N. fosliei , 0.63 mm · year −1 in N. brassica‐florida and 0.57 mm · year −1 in Neogoniolithon sp. The annual mean marginal elongation rate for these taxa was respectively 8.74, 13.92, 3.59, 9.40 and 9.25 mm · year −1 , with the exception of Neogoniolithon sp., for which this parameter was not recorded. Maximum marginal elongation occurred in P. onkodes pointing out its greater ability as a space competitor in comparison with the other rhodolith species. The highest accretion rate and common presence of L. kotschyanum indicate its importance as carbonate producer in tropical reef.

Microbialite formation in southern Sinai (Egypt) - Daniela Basso; Valentina Alice Bracchi; Andrea Noemi Favalli (Facies, 2013)

Pitavastatin, a new HMG-CoA reductase inhibitor, induces phototoxicity in human keratinocytes NCTC-2544 through the formation of benzophenanthridine-like photoproducts - Giampietro Viola; Pawel Grobelny; Maria Antonella Linardi; Alessia Salvador; Stefano Dall’Acqua; Łukasz Sobotta; Jadwiga Mielcarek; Francesco Dall’Acqua; Daniela Vedaldi; Giuseppe Basso (Archives of Toxicology, 2012)

Hydrolithon spp. (Rhodophyta, Corallinales) overgrow live corals (Cnidaria, Scleractinia) in Yemen - Francesca Benzoni; Daniela Basso; Annalisa Caragnano; Graziella Rodondi (Marine Biology, 2011)

Onset of temperate carbonate sedimentation during transgression in a low-energy siliciclastic embayment (Pliocene of the Val d’Orcia Basin, Tuscany, Italy) - Ronald Nalin; Massimiliano Ghinassi; Daniela Basso (Facies, 2010)

Use of Sugar Cane Vinasse to Mitigate Aluminum Toxicity to Saccharomyces cerevisiae - Ricardo Pinheiro de Souza Oliveira; Beatriz Rivas Torres; Mario Zilli; Daniela de Araújo Viana Marques; Luiz Carlos Basso; Attilio Converti (Archives of Environmental Contamination and Toxicology, 2009)

A model of area fidelity, nomadism, and distribution patterns of loggerhead sea turtles (Caretta caretta) in the Mediterranean Sea - Paolo Casale; Daniela Freggi; Roberto Basso; Carola Vallini; Roberto Argano (Marine Biology, 2007)

Biostratigraphic, paleobiogeographic and paleoecological implications in the taxonomic review of Corallinaceae - Daniela Basso; Patrizia Favega; Michele Piazza; Grazia Vannucci (Rendiconti Lincei. Scienze Fisiche e Naturali, 1998)

The taxonomy ofLithothamnium ramosissimum (Gümbel nonReuss)Conti andLithothamnium operculatum (Conti)Conti (Rhodophyta, Corallinaceae) - Daniela Basso; Patrizia Fravega; Grazia Vannuci (Facies, 1997)